PREVALENCE AND RISK FACTORS FOR INFANTILE COLIC IN DISTRICT MANSEHRA - Fazil, Mohammad (Journal of Ayub Medical College Abbottabad, 2011)
Objective: Infantile colic is a common problem among infants age 3 days to 3 months. It may affect parental feelings negatively and the parents may undertake all kinds of actions to stop excessive crying. The objective of this study was to assess the incidence of infantile colic and its risk factors in infants born in District Mansehra. Methods: In this prospective study, all those newborn babies were included who were born at King Abdullah Teaching Hospital Mansehra between January 1st 2008 and March 31, 2008, and those newborn babies who were brought to children OPD for routine check-up and EPI centre for vaccination of this hospital during this time period. For every infant, gender, mode of delivery, gestational age at birth, birth weight, birth order, and mother’s reproductive history were collected. These babies were seen at least once in a week up to 12 weeks and history from the mothers about the duration of crying and fussiness behaviour was recorded. At the end of 3 months the infants were again assessed and additional information on infant nutritional source was obtained and any medication used for colic relief was identified. Cases of colic were identified by applying Wessel criteria to recorded data. Chisquare tests were used. Results: From total 512 infants, follow-up was completed for 426 infants. In total, 90 infants (21.77%) satisfied the Wessel criteria for infantile colic. No statistical significance was found between colicky and non-colicky infants according to sex, gestational age at birth, birth weight, type of delivery, and, infant’s feeding pattern. However, firstborn infants had higher rate for developing colic (p=0.03). Conclusion: Prevalence of colic was 21.77% in this infant population of District Mansehra. Except for birth order, no other variable was significantly associated with infantile colic. Keywords: Infantile colic, Prevalence, Risk factors